Design of low glycemic response foods using polyphenols from seaweed. (May 2019) - Parada, Javier; Pérez-Correa, José R.; Pérez-Jiménez, Jara
Graphical abstract: Highlights: Seaweed has potential as source of functional ingredients for glycemic control. Selective inhibition of enzymes could optimize the homeostasis of glycaemia. Seaweed's non-extractable polyphenols are a promissory still little explored group. Design of functional food requires multidisciplinary efforts to cover all aspects. Abstract: Several aspects of foods affect starch digestion and glycemic response, including food's physical/chemical structure and the presence of anti-enzymatic compounds. The complex relationship between food properties, metabolism and diseases implies that designing foods with a consistent lower glycemic response turn challenging. Edible seaweeds are rich in several bioactive compounds -particularly polyphenols-, which can be used to develop new low glycemic response foods. This paper reviews what is known about functional ingredients found in seaweeds that may help to design lower glycemic response foods through mainly the inhibition of digestive enzymes related with the breakdown of glycemic carbohydrates. A global viewpoint is exposed, covering aspects related with seaweed's polyphenols composition and application of such compounds to design new products.